Clinical presentation, natural history, and cumulative death rates of 230 adults with primary cryptococcal meningitis in Zambian AIDS patients treated under local conditions. Issue 914 (1st December 2001) - Mwaba, P; Mwansa, J; Chintu, C; Pobee, J; Scarborough, M; Portsmouth, S; Zumla, A
Abstract : SETTING: Inpatient medical wards, Department of Medicine, University Teaching Hospital, Lusaka, Zambia. OBJECTIVE: To define the natural history, clinical presentation, and management outcome of microbiologically confirmed cryptococcal meningitis in adult AIDS patients treated under local conditions where antifungal and antiretroviral therapies are not routinely available. DESIGN: A descriptive, longitudinal, observational study. METHODS: All adult patients admitted to the medical wards of the University Teaching Hospital, Lusaka, Zambia with cerebrospinal fluid culture proved, primary cryptococcal meningitis, during a 12 month period were enrolled into the study. The following details were acquired: clinical features, HIV status, laboratory data, treatment accorded, and survival. RESULTS: A total of 230 patients with primary cryptococcal meningitis were studied (median age 32 years; range 15–65 years; 112 males, 118 females). Cryptococcal meningitis was the first AIDS defining illness in 210 (91%) patients. One hundred and thirty of the 230 (56%) patients had received treatment with fluconazole monotherapy and 100 (43%) patients received palliative care only without any antifungal therapy. A 100% case fatality rate was observed in both groups at follow up: by seven weeks in the untreated group and at six months in the fluconazole treated group. The cumulative median survival from time of diagnosis was 19 days (range 1–164 days) for the fluconazole treated group and 10 days (range 0–42 days) for the untreated group. CONCLUSION: Cryptococcal meningitis, under current treatment accorded at the University Teaching Hospital, Lusaka, has a 100% mortality in young Zambian adults with AIDS. The current treatment accorded to Zambian adults with cryptococcal meningitis is inappropriate. An urgent need exists to improve strategies for the clinical management of AIDS patients in poor African countries. The wider ethical and operational issues of making available antifungals to African AIDS patients are discussed.